8. Early Pregnancy Diagnosis Using Progesterone Kits in Local Goat (Capra hircus) - Agung - Kusasti; Ginta Riady; Cut Nila Thasmi; Dasrul Dasrul; Hamdan Hamdan; Sugito Sugito (Universitas Syiah Kuala, 2017)
This study aims to determine the effectiveness and accuracy of progesterone kit as a means of early pregnancy diagnosis in local goat. This study used 10 lactating female goats with weighing in the range of 35-51 kgs and the ages ranging from 2.0 to 2.5 years old. The sampled female goats are subject to estrus synchronization protocol using controlled internal drug release for goats (CIDR-G) inserted intravaginally for ten days and followed with prostaglandin injection on day 8 during progesterone implant insertion. Estrus detection was carried out with the introduction of one buck for 72 hours following the removal of the implants. Early pregnancy diagnosis using milk progesterone kits was carried out on day 17 following services. The accuracy of the kits for early pregnancy diagnosis was subsequently confirmed using USG examination on day 35 following services. The results of this study showed that oestrous response was 80%. Pregnancy diagnosis using progesterone kits and subsequently confirmation using USG were carried out in eight goats. All female goats showed positive results following pregnancy diagnosis using the kits both days 17 and 24 following services. Following confirmation on the pregnancy status using USG, one sampled goat was diagnosed non-pregnant. It could be concluded that the progesterone kit as can be used as an early pregnancy diagnosis tool in local goats on 17 days following services